1981
DOI: 10.1111/j.1445-5994.1981.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase Phenotypes in Patients with Diabetes Mellitus

Abstract: Glyoxalase phenotypes in patients with diabetes mellitus.Caucasian diabetic patients in Australian surveys showed a significant difference in the distribution of glyoxalase phenotypes. Insulin dependent diabetic patients with age of onset less than 40 years had a relative excess of glyoxalase homozygote 1-1 and a deficiency of types 2-7 and 2-2. Non-insulin dependent diabetic patients were not significantly different from non-diabetic subjects in the distribution of glyoxalase phenotypes.Insulin dependent diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…-The GLO genetic locus has been linked to insulin-dependent diabetes mellitus. A study of GLO gene frequencies has shown that there is a significant excess of glyoxalase homozygote GLO 1-1 and a deficiency of types GLO 2-1 and GLO 2-2 in insulindependent diabetic patients relative to controls (McCann et al, 1981). A GLO1 allele frequency in insulin-dependent diabetes higher than in non-diabetic patients was reported by Cambdonde Mouzon et al (1982).…”
Section: Biological Effects Of Methylglyoxalmentioning
confidence: 84%
See 3 more Smart Citations
“…-The GLO genetic locus has been linked to insulin-dependent diabetes mellitus. A study of GLO gene frequencies has shown that there is a significant excess of glyoxalase homozygote GLO 1-1 and a deficiency of types GLO 2-1 and GLO 2-2 in insulindependent diabetic patients relative to controls (McCann et al, 1981). A GLO1 allele frequency in insulin-dependent diabetes higher than in non-diabetic patients was reported by Cambdonde Mouzon et al (1982).…”
Section: Biological Effects Of Methylglyoxalmentioning
confidence: 84%
“…For non-insulin-dependent diabetic patients, Kirk et al (1979) found an excess of GLO 2-2 phenotype and a deficiency of GLO 1-2 phenotype whereas other surveys (Kirk et al, 1985;McCann et al, 1981) produced no significant difference. However, more interestingly, insulin-dependent diabetic patients without clinical complications had a significant excess of the homozygote GLO 1-1 whereas patients with complications did not (McCann et al, 1981). Our experimental results have suggested that there is a correlation between glyoxalase activities and the development of clinical complications in insulinVol.…”
Section: Biological Effects Of Methylglyoxalmentioning
confidence: 85%
See 2 more Smart Citations
“…there was a significant disturbance in GLO phenotype distribution: an increase in Gb 1-1 homozygote (McCann et al, 1981;Cambdon de Mouzon et al, 1982) or an increase in Gb 1-2 heterozygote (Kirk et ab., 1985). Other surveys (Allannic et al, 1985;Kirk et al, 1979) found no significant difference between IDDM patients and controls.…”
Section: For Insulin-dependent Diabetes Mellitus (Iddm)mentioning
confidence: 99%